Twitter Posts About Cannabis Use During Pregnancy and Postpartum:A Content Analysis. (7th June 2021) - Pang, Raina D.; Dormanesh, Allison; Hoang, Yannie; Chu, Maya; Allem, Jon-Patrick
Abstract: Background: The prevalence of cannabis use has increased among U.S. pregnant women. Given this increase, and rapidly changing cannabis policies, it may be important to harness digital data sources to help capture trends and perceptions of cannabis use during pregnancy and postpartum. The objective of this study was to examine cannabis and pregnancy-related posts on Twitter over a 12-month period. Methods: Twitter posts from December 1, 2019 to December 1, 2020 that contained pregnancy and cannabis-related keywords were collected in this study ( n = 17, 238). A sample of 1, 000 posts proportionally sampled by week and cannabis/pregnancy-related terms were selected for coding. Posts were classified by one or more of the following themes: 1) Safety during pregnancy i.e. mentions the safety of cannabis use during pregnancy, 2) Safety postpartum i.e. mentions the safety of cannabis use postpartum, and 3) Use for pregnancy-related symptoms i.e. mentions use of cannabis to help with morning sickness, nausea, vomiting, headaches, pain, stress, and fatigue. Results: Safety during pregnancy occurred in 36.00% of the posts and 2.30% posts asked about safety during postpartum. Use of cannabis for pregnancy-related symptoms occurred in 2.70% of posts. Discussion: Findings show that conversations about the risks and benefits of cannabis use during pregnancy and postpartum take place on Twitter. These findings suggests that health practitioners should discuss the risks of cannabis use (including CBD) during pregnancy and breastfeeding with their patients. Health communication planners may need to find ways to communicate risks with the public to prevent the spread of misinformation.